Comparison of cure rates and durations of treatment with diphenylcyclopropenone immunotherapy for warts in children/adolescents and adults. (2nd April 2014) - Kang, Ho Song; Lee, Min Won; Paek, Jun Oh; Yu, Hee Joon; Kim, Joung Soo
Abstract Background Immunotherapy has been used for many years in the treatment of warts. Diphenylcyclopropenone is frequently used as an immunotherapeutic agent. Methods A total of 143 patients with 180 cases of warts were included in this study. We divided the patients into two groups: 72 children/adolescents and 71 adults aged 20 and over. We evaluated two types of sensitization reaction, using an erythema and blister index and a pruritus index. Results Of the 180 cases of warts, 159 (88.3%) were completely cured: 86 (92.5%) of the 93 cases in children/adolescents and 73 (83.9%) of the 87 cases in adults. The time required for complete cure was 17.72 ± 2.69 weeks in children/adolescents and 22.92 ± 2.59 weeks in adults (P < 0.05). Conclusions Diphenylcyclopropenone immunotherapy can be used effectively for both children/adolescents and adults. The time required for complete cure is shorter in children/adolescents than in adults.